Ensembles and uncertainty in climate change impacts - Falloon, Pete; Challinor, Andy; Dessai, Suraje; Hoang, Lan; Johnson, Jill; Koehler, Ann-Kristin (Frontiers in Environmental Science, 2014)
The increasing use of multi-member climate model ensembles for making future climate impact assessments presents both opportunities for understanding uncertainties, and challenges for interpreting the results. We outline current approaches to assessing uncertainties in climate impacts, statistical methods for assessing uncertainties, issues regarding model integration and complexity, and ways in which uncertainty frameworks can be used to inform adaptation decisions, with case studies focused on agriculture. Finally, we highlight future research needs and provide recommendations for making further progress.